NHBA antibodies elicited by 4CMenB vaccination are key for serum bactericidal activity against Neisseria gonorrhoeae - Yih-Ling Tzeng; Soma Sannigrahi; David S. Stephens (npj Vaccines)
Abstract The 4CMenB (BexseroR) vaccine contains detergent-extracted outer membrane vesicles (OMVs) from a Neisseria meningitidis (Nm) group B strain NZ98/254 and three recombinant Nm protein antigens: Neisseria adhesin A (NadA), Factor H binding protein (FHbp, as the C-terminal protein in the GNA2091-FHbp fusion), and Neisserial Heparin Binding Antigen (NHBA, as the N-terminal protein in the NHBA-GNA1030 fusion). Previous work has shown that 4CMenB generates serum antibodies to Nm and Neisseria gonorrhoeae (Ng) OMV proteins and lipooligosaccharide (LOS). Mounting evidence indicates 4CMenB can partially protect against mucosal infections with Ng. The immunologic basis for Ng cross protection remains to be fully elucidated. Ten paired human sera obtained pre- and post-immunization with 4CMenB (1 month after a third vaccine dose) were used in ELISAs and in Western blots to determine IgG and IgA serum responses to OMVs from Nm strain NZ98/254 (OMVNm) and two Ng strains, 1291 and CNG20 (OMVNg), and gonococcal recombinant NHBA (rNHBANg) proteins. Post 4CMenB sera, but not pre-sera, showed strong IgG and variable IgA responses to the OMVNm but lower (2–11-fold difference in signal intensity) recognition of OMVNg. All post (not pre) 4CMenB sera showed strong IgG, but variable IgA, recognition of rNHBANg by ELISAs and Western blots. Three post 4CMenB sera at 10% (v/v) concentration had serum bactericidal activity (SBA) against Ng strains 1291 and CNG20 (~30–40% killing), not seen in paired pre-sera. These data confirmed 4CMenB-induced cross-reactive functional antibody responses to Ng. In competitive SBA assays, in which sera were pre-incubated with rNHBA, minimal SBA against Nm strain NZ98/254 was titrated away. However, most of the SBA against Ng strains 1291 and CNG20 required NHBA-specific antibodies, and the Δnhba mutants were resistant to killing by post 4CMenB sera. Removing NHBA-specific and LOS-specific OMV antibodies simultaneously decreased SBA significantly more than the sum of removing individual antibodies alone, suggesting synergy between anti-NHBA and anti-OMV antibodies. Anti- NHBANm antibodies induced by 4CMenB vaccination cross react with NHBANg and substantially contribute to the bactericidal response toward Ng induced by the vaccine.